Else K. Holt, Narrative and Other Readings in the Book of Esther, Library of Hebrew Bible / Old Testament Studies 712, Bloomsbury, T&T Clark, London UK 2021, pp. 172. - Trojanowska, Mariola (Collectanea Theologica, 2021)
.